Good Manufacturing Practice Sebagai Strategi Peningkatan Mutu Pangan Produk UMKM Berkah Rangga, Kubu Raya - Wardanu, Uliyanti; Fera Maulina; Fransiska (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Processed food MSMEs are strategically supporting food security while contributing to the community's economy. However, one of the significant challenges is the low implementation of Good Processed Food Production Methods (CPPOB), which results in inconsistent product quality and safety. This condition is also experienced by Berkah Rangga (BR) MSME in Kubu Raya Regency, which, despite having business legality, still faces problems such as uncontrolled raw material quality, limited knowledge of sanitation and hygiene, and the absence of standardized operational procedures (SOP) in production. This community service program aimed to strengthen the partner's capacity in implementing CPPOB through a Participatory Action Research (PAR) approach. The program was carried out from July to August 2025. It consisted of several stages: socialization, training using a learning by doing approach, hygienic practice assistance, and evaluation through knowledge tests, interviews, and observations. The results showed that participants' understanding of CPPOB significantly improved, achieving a perfect score (80/80) on all evaluation items. Before the program, partners had a basic understanding of CPPOB but were weak in applying sanitation practices. After the program, there was a noticeable improvement in workplace cleanliness, better organization of raw material storage, and awareness of applying simple SOPs. Although participants' motivation varied due to limited facilities, mentoring encouraged more hygienic production behavior. The outcomes of this program are important for improving satisfaction and providing tangible benefits in strengthening a culture of quality, enhancing food safety, and increasing the competitiveness of BR MSME in both local and broader markets.